Analysis of drug interactions and epidemiological profile of individuals with diabetes mellitus in primary care - Zanatta, Leila (2020)
Aim: to analyze drug interactions and the epidemiological profile of individuals with diabetes mellitus (DM). Method: quantitative study with the application of a questionnaire to 42 patients with DM belonging to a Family Health Center (FHC). Data were collected in 2018, in three stages: meeting at the CSF, home visits and searching electronic medical records; followed by analysis of drug interactions in the Drug Interactions Checker Drug Information and DrugBank databases. Results: the mean age of the patients was 68.36 years. The total number of associations between drugs was 1355 (mean 32.26 / patient). The total number of medications that interact was 479 (11.40 interactions /patient). In 65% the combinations did not interact, 4% were mild interactions, 26.05% moderate and 1.70% severe. Conclusion: the number of drug interactions is significant, with a moderate degree predominating. The age of patients and the presence of comorbidities can be associated with polymedication, contributing to the occurrence of these interactions.